Menopausal status, age and management among women living with HIV in the UK. Issue 9 (26th July 2021) - Okhai, Hajra; Sabin, Caroline A.; Haag, Katharina; Sherr, Lorraine; Dhairyawan, Rageshri; Burns, Fiona; Gilson, Richard; Post, Frank; Ross, Jonathan; Mackie, Nicola; Sullivan, Ann; Shepherd, Jane; et al.
Abstract: Background: There is currently little evidence exploring menopausal status, age at last menstrual period (LMP) and management of menopause among women living with HIV aged 45–60 years in England. Methods: Socio‐demographic, lifestyle and clinical data were collected through a self‐completed cross‐sectional survey. Longitudinal CD4 count and viral load data were available from linkage to clinical records, if consent was provided. Women were categorised as pre‐, peri‐ or post‐menopausal. Factors associated with menopausal stage were examined using ordinal logistic regression adjusting for age. Age at LMP was estimated using Kaplan–Meier survival analysis. Results: The 847 women had a median age of 49 [interquartile range (IQR): 47–52] years. Most were of black ethnicity (81.3%), were born outside the UK (85.0%) and had completed secondary education (88.7%); 177 (20.4%), 373 (43.0%) and 297 (34.2%) were pre‐, peri‐ or post‐menopausal, respectively. After adjusting for age, associations of menopausal status with non‐cohabiting relationship [adjusted odds ratio = 0.63 (95% confidence interval: 0.43–0.91)], baseline viral load ≥ 100 000 copies/mL [2.67 (1.20–5.94)] and unemployment [1.34 (0.97–1.84)] remained significant. Median (IQR) age at LMP was 54 (51–55) years in the group. In total, 27.9% (233/836) of women reported severe menopausal symptoms; 45.6% of those with somatic symptoms had heard of hormone replacement therapy and 8.7% had used it. Only 5.6% of women with urogenital symptoms had used topical oestrogen. Conclusions: Our findings highlight the importance of educating both women and their healthcare providers about menopausal symptoms and management options.